REASONABLE TIME FRAME IN THE BANKRUPTCY PROCEEDING: ANALYSIS OF CASES BEFORE THE COMMERCIAL COURT IN NIŠ - Mojašević, Aleksandar; Jovanovic, Aleksandar (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The Law on the Protection of the Right to a Trial within a Reasonable Time, which took effect in 2016, has created the conditions in our legal system for the protection of the right to a trial within a reasonable time, as one of the fundamental rights guaranteed by the Constitution of the Republic of Serbia as well as related international documents. Although it not has been explicitly provided for the application of the Law in the context of the bankruptcy proceeding, it has served in practice as a mean for the bankruptcy creditors to obtain fair satisfaction because of the long duration of this proceeding and the violation of the right to a trial within a reasonable time. Therefore, the subject of the analysis in this paper is a procedure that protects the right to a trial within a reasonable time for bankruptcy cases. The paper aims to examine whether the complaint, as an initial act, as well as the procedure for the protection of rights, is a suitable instrument for increasing the efficiency of the bankruptcy proceeding, taking into account the particularity and complexity of the bankruptcy proceeding. The authors will also examine whether this remedy affects the overall costs of the bankruptcy proceeding and whether and how long it extends the duration of the proceeding. For this purpose, a case study will be conducted on cases within the jurisdiction of the Commercial Court in Niš in the period from the beginning of application of the Law (2016) to the end of 2019.